2012
DOI: 10.3174/ajnr.a3102
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Stroke Penumbra: Use of National Institutes of Health Stroke Scale as a Surrogate for CT Perfusion in Patient Triage for Intra-Arterial Middle Cerebral Artery Stroke Therapy

Abstract: BACKGROUND AND PURPOSE: CTP may help triage acute stroke patients for IAT, but requires additional contrast agent, radiation, and imaging time. Our aim was to determine whether clinical examination (NIHSS) with NCCT and CTA can substitute for CTP without significantly affecting IAT triage of patients with acute MCA stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…In all of the above discussions, the concept of penumbra is evaluated using a combination of the severity of the clinical deficit and location of the LVO. This concept is the ‘clinical penumbra’, or ‘clinical–diffusion mismatch’ 65. When this approach is used, no additional physiologic imaging is used to categorize the volume of tissue at risk.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all of the above discussions, the concept of penumbra is evaluated using a combination of the severity of the clinical deficit and location of the LVO. This concept is the ‘clinical penumbra’, or ‘clinical–diffusion mismatch’ 65. When this approach is used, no additional physiologic imaging is used to categorize the volume of tissue at risk.…”
Section: Methodsmentioning
confidence: 99%
“…CT perfusion is at a greater disadvantage, since both core infarct and penumbral volumes depend on post-processing calculations, as opposed to MR-DWI, which preserves a sensitive physiological marker of irreversible infarction (restricted diffusion of water in infarcted tissue). Owing to these drawbacks of perfusion imaging (CTP or MR-PWI), some have postulated that a surrogate for the penumbra may simply be reflected by the patient's clinical examination or NIHSS 65. At this time, the clinical penumbra may be the best indicator to select patients for embolectomy as long as an accurate and small core infarct estimate is available.…”
Section: Methodsmentioning
confidence: 99%
“…One investigation found no combination of CT ASPECTS and NIHSS predicted perfusion–diffusion mismatch ( 97 ) and another study found no relationship between “clinical–CT mismatch” and likelihood of responding to IV tPA ( 98 ). Researchers have also shown that EVT decisions were changed rarely (5.6%) when including CTP in addition to NIHSS, non-contrast CT and CTA ( 99 ).…”
Section: Moving Beyond the Clock: Shifting The Paradigm From “Time Ismentioning
confidence: 99%
“…Patients arriving at the authors' hospital within 4.5 hours of symptom onset are candidates for IV thrombolysis. 8,9 IV therapies must be initiated within a strict time limit to avoid unacceptable rates of intracranial hemorrhage. The therapeutic window for administration of IV rt-PA was extended from 3 to 4.5 hours based on the outcome of European Cooperative Acute Stroke Study III (ECASS III).…”
Section: Algorithmic Approach To Ischemic Strokementioning
confidence: 99%